2011
DOI: 10.1001/archinternmed.2010.536
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alcohol Intake With Pancreatic Cancer Mortality in Never Smokers

Abstract: These results strengthen the evidence that alcohol consumption, specifically liquor consumption of 3 or more drinks per day, increases pancreatic cancer mortality independent of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 33 publications
5
68
1
Order By: Relevance
“…Thus these results are representative of the US population. The mean risk of death in the study population for pancreas cancer was 0 .0014 ( Alcohol consumption has been associated with increased pancreas cancer mortality (Gapstur et al, 2011) and this was confirmed here. This study found the relationship between poverty and pancreas cancer death was more complex.…”
Section: Discussionsupporting
confidence: 82%
“…Thus these results are representative of the US population. The mean risk of death in the study population for pancreas cancer was 0 .0014 ( Alcohol consumption has been associated with increased pancreas cancer mortality (Gapstur et al, 2011) and this was confirmed here. This study found the relationship between poverty and pancreas cancer death was more complex.…”
Section: Discussionsupporting
confidence: 82%
“…3 Never exposed to HBV. 4 Chronic carrier of HBV. 5 Previously exposed to HBV with immunity, but possibly harboring persistent HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…1 Almost all patients die of the disease within 1 year of the diagnosis, with conventional treatments having little impact on disease course. Several risk factors associated with pancreatic cancer have been explored, including genetic, 2 cigarette smoking, 3 alcohol intake, 4 chronic pancreatitis, 5 diabetes mellitus, 6 obesity, 7 first-degree relatives of pancreatic cancer 8 and Helicobacter pylori infection. 9 Nevertheless, these factors account only for a minority of cases, the causative environmental and genetic factors for pancreatic cancer still remain unknown.…”
mentioning
confidence: 99%
“…Early identification of individuals at high risk for pancreatic adenocarcinoma could have a marked impact on reducing morbidity and mortality. Several risk factors associated with pancreatic cancer have been identified, including genetic factors [5], cigarette smoking [6,7,8,9], alcohol intake [10], chronic pancreatitis [11,12], diabetes mellitus [13,14], and obesity [15,16,17]. However, most of these risk factors were identified by systematic reviews of Western studies, and risk factors for pancreatic adenocarcinoma in China have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%